Seasonal Growth and Instability of Ring Seine Fishery in Kerala - Dhiju Das, P. H.; Sruthi, P.; Gopal, Nikita; Edwin, Leela (Fishery Technology, 2018)
Ring seine, which is the major fishery of Kerala, contributes 55.7% of the state’s total marine fish production and contributes 21.31% of the total marine landings of the country, out of which 73.4% is of pelagic resources. Even small fluctuation in the annual output of ring seine reflects on the total fish production of the state. Two types of ring seine systems are operating in Kerala, namely, mechanised (fitted with inboard motors or IBM) and motorized (operated with outboard motors or OBM). This paper examines the growth and instability of fish production from the ring seiners operating from central Kerala, India during the period 2002-2011. Time series data on daily landing from 36 fishing vessels, including 27 mechanised and 9 motorized ring seine units were used for the study. The results reveal that there is a positive growth in the production from the mechanised ring seiners while the growth from the motorized sector has been falling over the period under study. The overall instability ranged from 36-38% and was more prominent in motorized vessels.